Analisis Multimodal terhadap Strategi Komunikasi Pemasaran Seblak Inceess di Media Sosial Instagram - Farisya Tsani Pandora; Oky Oxcygentri; Ema Ema (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The development of social media, especially Instagram, encourages business actors to optimize visual and narrative-based marketing communication strategies. One form of this strategy is the use of multimodality in delivering promotional messages. This study aims to analyze the multimodal-based marketing communication strategy implemented by the culinary brand Seblak Inceess through its official Instagram account. This study uses a descriptive qualitative approach with a multimodal analysis method based on the theory of Kress and van Leeuwen which includes three metafunctions, namely representational, interpersonal, and compositional metafunctions. The primary data consists of twelve Instagram posts from the @seblakinceess account which were selected purposively based on the highest level of impressions in the period January–December 2025. Data collection techniques were carried out through observation and documentation, while data analysis was carried out descriptively interpretatively. The results show that Seblak Inceess utilizes a combination of visual elements, text, audio, and audience interaction in an integrated manner to build a brand image that is close, relaxed, and relevant to the audience's daily lives. The marketing communication strategy implemented tends to be entertainment-based soft selling, where promotional messages are conveyed subtly through narrative content and attractive visuals. These findings indicate that a multimodal marketing communication strategy on Instagram is effective in increasing audience engagement and building emotional closeness between brands and consumers.